(untitled) (Journal of Intellectual Property Rights (JIPR), 2025)
ntellectual Property Rights play an important role in protecting inventions from Infringement, nowadays academic Institutions have started to set up IPR cell and Technology Transfer Office (TTOs) in their premises, not only to protect the inventions by filing various IPRs through IPR cell, but also for the commercialization/licensing of IPRs filed in the name of Academic Institution. This study investigates the strategies and practices surrounding technology transfer of IPRs in academic institutions, with a particular focus on how these institutions facilitate the commercialization of research. The research explores the role of Technology Transfer Offices (TTOs), key challenges in the transfer process, and the impact of effective technology transfer on institutional revenue generation. Using a qualitative approach, data were collected from academic professionals involved in technology transfer, analysing aspects such as intellectual property rights (IPRs) filed, transactions completed, and the factors that hinder or promote successful technology transfer. The findings highlight the significance of robust TTOs in promoting innovation and the commercialization of academic research while also identifying common barriers, including inadequate funding, bureaucratic inefficiencies, and limited industry collaboration. The study concludes by offering recommendations for improving the effectiveness of technology transfer offices in India, such as policy reforms, enhanced industry partnerships, and capacity-building efforts.